Efektivitas Alat Pencuci Gelas Otomaris (PILOT) Berbasis Arduino Nano - Mokhamad Arif Rachman Rosyidi; Maulidina, Miftakhul; Puspitasari, M. Dewi Manikta (Nusantara of Engineering (NOE), 2022)
Washing glass in large quantities will definitely be tiring and take a long time, the author tries to develop an Arduino Nano-based automatic glass washer (PILOT). In addition to being useful in the culinary industry, it is also useful in the household, especially helping to ease the task of housewives. The purpose of this study is (1) to compare how fast the PILOT glass washing tool is with manual washing (2) to find out how effective the PILOT automatic glass washing tool is with manual glass washing. This research uses quantitative research type. Quantitative Research Methods, namely research methods used to examine certain populations or samples, data collection using quantitative/statistical data analysis. Based on the results of testing on glass washers using the PILOT tool, it can be concluded that: (1) the speed of the PILOT tool in washing glass is superior to manual washing. (2) the washing speed based on the type of stain on the PILOT tool is more effective than manual washing (3) the results of data collection using the PILOT automatic glass washer questionnaire reached an average of 80% while the average results from manual glass washing reached 80%. With the same value results, but the PILOT tool is more superior because its use can automatically make it easier for users to wash glasses and save more energy, especially washing glasses in large quantities.